Email marketing and E-CRM - Hughes, David (Henry Stewart Talks, 2010)
Advantages of e-mail marketing, Finding the right broadcasting partner, Bad e-mail marketing, Bad e-mail marketing can be good e-mail marketing, Non-line marketing, Don't wave goodbye to direct mail, Segmentation and personalization, Registration: a critical part of e-mail marketing, Transactional data, Lifecycle marketing, Click-stream data, The landing page, Think about the customer journey
Archived at 2022/04/12